COGNITIVE LINGUISTICS AND METHODOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses semantics, which is a part of cognitive linguistics. Metonymy is analyzed from the methodological field of the semantic field.